Bürger:innen als Frühwarnsysteme (Public Health Sentinels) in der öffentlichen Gesundheit: Fokusgruppen zur Teilnahme an einer adaptiven und kontextsensitiven Echtzeitkohortenstudie in Krisenzeiten: Leitthema - Zintel, Stephanie; Hennig, Hannah; Jones, Christopher; Araújo-Soares, Vera; Andreas, Marike; Hoffmann, Kristina; Kramer, Birgit; Mergarten, Björn; Schneider, Sven; Sniehotta, Falko F.; Kaiser, Anna K. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2025)
Background The COVID-19 pandemic has highlighted the need for high-resolution evidence on the social and contextual conditions as well as health outcomes of such emergency events. The PULS (Populationsbasierte Umfrage zur Lebenssituation und Sozialen Gesundheit, i.e., Population-Based Survey on Living Conditions and Social Health) study aims to provide such evidence with an agile and responsive real-time cohort. Here, we examine the determinants of participation in such a study. Methods A qualitative study using seven semi-structured focus groups (between 16 December 2024 and 14 February 2025), each with 4 to 7 participants (total of 22 men, 17 women, 2 non-binary individuals; diverse backgrounds). Statements were deductively coded along the 14 domains of the Theoretical Domains Framework. Results Participants primarily emphasized the importance of various aspects associated with the domains of Reinforcement, Beliefs about Consequences, Environmental Context and Resources, and Goals, and Beliefs about Capabilities. However, participants did not only mention distinct aspects but also weighed them against each other. For example, participants were more willing to invest resources such as time if the resulting political and social implications of the study aligned with their personal goals, thus demonstrating a subjective contribution to the common good. Discussion Participation in an agile, responsive, and long-term cohort study is viewed acceptable and feasible under certain conditions. The perceived impact on society and politics as well as the translation of research into policy seem to be key incentives for citizens and can outweigh personally invested resources. These results have implications not only for the implementation of the PULS study but also for the related translation pathways.